“Geseënd en gewyd” – Handoplegging en bevestiging by Calvyn, asook in die gereformeerde tradisie ná hom - Coertzen, P (Nederduitse Gereformeerde Teologiese Tydskrif, 2006)
“Blessed and Consecrated” – The laying on of hands and ordination in the thought of John Calvin and the reformed tradition after him The article is about ordaining in Reformed Churches. It starts of with a few examples of how the office of the minister and the act of ordainment is viewed in reformed theology and church practice. Then it goes on to analyse what John Calvin said about it – the fact that he was prepared to call it a third sacrament. The article continues to look at the views of church politicians after Calvin as well as some Reformed church orders since the sixteenth century right up to our own day. The conclusion is that it can be worth the while for reformed theology to again listen to the largely unknown and therefore unappreciated thoughts of John Calvin on the ordaining of ministers.